Electronic Structure of a Molecular Magnet from Salicylate Based Copper Complex - Tho, Nguyen Duc; Trang, Nguyen Thuy; Nhat, Hoang Nam (VNU Journal of Science: Mathematics - Physics; Vol 28 No 1, 2012)
Abstract. The electronic structure of the metallo-organic compound Cu(SA) 2 (2-PM) 2 (2-PM is 2-pyridylmethanol) is presented. The calculation was performed using the Density Functional Theory with unrestricted spin polarized model and large wave function basis sets which include the polarized and diffuse functions. The single point energy calculation for the isolated molecule gave the HOMO-LUMO separation of 3.8 eV and the LDA+U band structure calculation showed the band gap of only 0.38 eV. The calculated magnetic moment per molecule is comparable to the experimentally observed value. Keywords: Molecular magnet, DFT, Electronic structure